Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
1
a) d = a√2
3 = a√2
[tex]\frac{3}{\sqrt{2} } = \frac{3\sqrt{2} }{2} = a[/tex]
[tex]P = a^{2} = (\frac{3\sqrt{2} }{2})^2 = \frac{9*2}{4} = 4,5[/tex]
b)
[tex]\sqrt{7} = a\sqrt{2}\\\frac{\sqrt{7}}{\sqrt{2} } = \frac{\sqrt{14} }{2} =a\\\\P = (\frac{\sqrt{14} }{2})^2=\frac{14}{4} =3,5\\[/tex]
2.
[tex]P = \frac{a^2\sqrt{3} }{4} \\h = \frac{a\sqrt{3} }{2}[/tex]
a)
[tex]P = \frac{6^2\sqrt{3}}{4} = \frac{36\sqrt{3} }{4} = 9\sqrt{3} \\h = \frac{6\sqrt{3} }{2} =3\sqrt{3}[/tex]
b)
[tex]P = \frac{(\sqrt{6})^2 \sqrt{3}}{4} = \frac{6\sqrt{3} }{4} = \frac{3\sqrt{3} }{2}\\h = \frac{\sqrt{6} * \sqrt{3}}{2} = \frac{\sqrt{18}}{2} = \frac{3\sqrt{2} }{2}[/tex]